A decade of Ecuador´s efforts to raise its health research output: a bibliometric analysis - Ivan Sisa; Andrea Abad; Isabel Espinosa; Isaac Martinez-Cornejo; Pablo Burbano-Santos (Global Health Action)
Background: Over the past decade, the political movement called ‘Revolución Ciudadana’ implemented a variety of policies and interventions (P&I) in Ecuador to improve higher education and strengthen local research capacity. We refer specifically to the ‘Mandato 14’ and the Higher Education Law (LOES, Spanish acronym) launched in 2008 and 2010, respectively. Objective: To assess the impact of these P&I (Mandato 14/LOES) on the production of health sciences-related articles (HSRA), and the relationship of these HSRA with the country’s health priorities. Methods: A Scopus search was performed to retrieve HSRA published from 1999 to 2017. Bivariate analysis was used to assess variation between the period I (1999–2008) and period II (2009–2017). Further, we examined the association between the top 10 causes of mortality and the total HSRA output. Results: The final study sample consisted of 2784 articles. After 2008, Ecuadorian production of HSRA increased steadily from 671 to 2133 publications (p<.001). Overall (1999–2017), the most common study design was cross-sectional (32.3%), the primary research focus was in the clinical-surgical area (49.3%), and the academic institutions were the primary drivers of scientific production during period II (56.9% vs. 29.5%, p<.001). Further, we found a decrease in the production of randomized controlled trials (6.7% vs. 1.8%, p<.001). Only 9% of research production involved the primary causes of mortality, and the proportion has remained unchanged over time (8.2% vs. 9.3%, p>.05). Conclusions: Ecuadorian HSRA output increased significantly after 2008. This larger volume of scientific output could be the result to the Mandato 14/LOES implemented in the last decade. However, a low percentage of HSRA are dedicated to addressing the country’s health priorities. Proper planning, execution and monitoring of national health research agendas would reduce the mismatch between health burden and the HSRA output in Ecuador and other low-and middle-income countries.